2011
DOI: 10.1007/s10571-011-9673-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Cell Phenotypes Differentiating from Mice Retinal Neurospheres Using Single Cell Calcium Imaging

Abstract: Degeneration of neural retina causes vision impairment and can lead to blindness. Neural stem and progenitor cells might be used as a tool directed to regenerative medicine of the retina. Here, we describe a novel platform for cell phenotype-specific drug discovery and screening of proneurogenic factors, able to boost differentiation of neural retinal progenitor cells. By using single cell calcium imaging (SCCI) and a rational-based stimulation protocol, a diversity of cells emerging from differentiated retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
4
13
0
Order By: Relevance
“…Third, we used calcium responses to different cell-specific stimuli to characterize bipolar cells triggered by microPH medium. We used Fura-2 AM, a cell permeant calcium indicator: KCl, which triggers an intracellular Ca ϩ2 response in excitable cells (De Melo Reis et al, 2011); AMPA, which depolarizes neurons expressing the corresponding glutamate receptors (Bloodgood and Sabatini, 2008); ATP, which activates purinergic receptors in astrocytes and neurons (De Melo Reis et al, 2011); histamine, which triggers intracellular Ca ϩ2 response in immature cells through histamine receptor, highly expressed on immature/stem cells and embryonic stem cells (Eiriz et al, 2011); and NMDA ( Fig. 11A-D).…”
Section: The Secretome From Phagocytic Microglia Drives Neuroprogenitmentioning
confidence: 99%
“…Third, we used calcium responses to different cell-specific stimuli to characterize bipolar cells triggered by microPH medium. We used Fura-2 AM, a cell permeant calcium indicator: KCl, which triggers an intracellular Ca ϩ2 response in excitable cells (De Melo Reis et al, 2011); AMPA, which depolarizes neurons expressing the corresponding glutamate receptors (Bloodgood and Sabatini, 2008); ATP, which activates purinergic receptors in astrocytes and neurons (De Melo Reis et al, 2011); histamine, which triggers intracellular Ca ϩ2 response in immature cells through histamine receptor, highly expressed on immature/stem cells and embryonic stem cells (Eiriz et al, 2011); and NMDA ( Fig. 11A-D).…”
Section: The Secretome From Phagocytic Microglia Drives Neuroprogenitmentioning
confidence: 99%
“…Neurite growth was assessed via confocal microscopy after immunostaining for Tuj-1. Variations in the free intracellular calcium level ([Ca 2+ ]i) were evaluated in DRG neurons or Schwann cells obtained from P1 DRGs following an adaptation of the protocol reported by de Melo Reis et al, 2011 [18] . DRG neurons and Schwann cells were seeded on poly-L-lysine- and laminin-coated coverslips for 48 h. The cells were loaded for 40 min with 5 µM Fura-2/AM (Molecular Probes) in Krebs solution (132 mM NaCl, 4 mM KCl, 1.4 mM MgCl 2 , 2.5 mM CaCl 2 , 6 mM glucose, 10 mM HEPES, pH 7.4) containing 0.1% fatty acid-free bovine serum albumin (BSA) and 0.02% pluronic acid F-127 (Molecular Probes) in an incubator containing 5% CO 2 and 95% atmospheric air at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we examined the calcium response of bipolar, stellate, and freshly dissociated NPCs to different stimuli using Fura-2 AM, a cell permeant calcium indicator: KCl, which triggers an intracellular Ca +2 response in excitable cells (De Melo Reis et al, 2011); AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid), which depolarizes neurons expressing the corresponding glutamate receptors (Bloodgood and Sabatini, 2008); ATP (adenosine triphosphate), which activates purinergic receptors in astrocytes and neurons (De Melo Reis et al, 2011); histamine, which triggers intracellular Ca +2 response in immature cells through histamine receptor, highly expressed on immature/stem cells and embryonic stem cells (Eiriz et al, 2011); and NMDA (N-methyl-D-aspartate) ( Figure 6A-D). We found that 69% of the freshly dissociated NPCs depolarized in response to ATP and histamine, and became hyperpolarized in response to KCl.…”
Section: The Secretome From Phagocytic Microglia Drives Neuroprogenitmentioning
confidence: 99%
“…In vivo no changes in the production of newborn astrocytes were observed in the neurogenic cascade, although on isolated NPCs the phagocytic microglial secretome gave rise to astrocytecommitted cells with a bipolar phenotype, reminiscent of radial glia (Encinas and Enikolopov, 2008). These cells presented several astrocytic features, including the expression of GFAP and S100β (Encinas and Enikolopov, 2008;Raponi et al, 2007); intracellular calcium response to ATP (De Melo Reis et al, 2011) and high phosphorylation of SMAD, which interacts with TGFβ to give rise to astrocytes/radial glia (Stipursky and Gomes, 2007). Nonetheless, our transcriptional assay did not show heterologous `gliogenic´ genes in phagocytic microglia, suggesting that rather than actively promoting astrogenesis, the acute phagocytosis secretome indirectly promote the default astrocytic lineage (Miller and Gauthier, 2007) by restricting the neuronal lineage.…”
Section: Microglia Regulates Neurogenesis Through the Phagocytosis Sementioning
confidence: 99%